THE DEVELOPMENT OF TOURISM VILLAGE BASED ON DIGITAL MANAGEMENT - Indra Hastuti; Sopingi Sopingi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this study was to obtain a model for developing a tourism village based on digital management, through e-marketing, e-tickets and e-reports for tourism villages. This study uses a qualitative research method with a simulation observation research strategy. Observations were made at the Sidowayah Klaten Tourism Village in the Siblarak banner, Dolanan village, Tobing tourism. The problem of the Sidowayah tourist village at this time is that there are few visitors and are local tourists around Klaten district, not yet known on a national scale, MSME products as souvenirs are not widely known to visitors. The research stages were carried out by identifying and mapping the tourism sector and MSME products owned by the Sidowayah Tourism Village, carried out using a qualitative descriptive method. The next stage is to build an application model for a tourism village development program based on digital management based on tourism and entrepreneurship, starting with designing digital marketing applications, e-tickets, e-reports, application testing and application implementation in Sidowayah Tourism Village Management. The results of the research are the mapping of the tourism sector and MSMEs and the application model for developing a tourism village based on Digital Management. From these results, it can solve problems in the development of Tourism Villages, including tourist villages that are easily known to the public, people who are going on vacation can choose tourist attractions and order tickets through the application, buy souvenirs for MSME products and tourism managers can find out ticket financial reports at any time.